Lawsuit for the Termination of the Joint Stock Company for Just Cause Under Turkish Law - Ay, Yunus Emre (Journal of Legal Studies, 2025)
Shareholder relations in a joint stock company may go well or may become unbearable over time. For this reason, the Turkish Commercial Code provides minority shareholders with the right to file a lawsuit for the termination of the joint stock company for just cause, especially for the protection of minority rights. The legislator has also allowed the judge to decide on alternative solutions instead of terminating the company for just cause. The legislator has not specified what constitutes just cause termination and has left this matter to the doctrine and judicial decisions. The purpose of this study is to clarify the issues left to the doctrine and judicial decisions in the light of the doctrine.